Knowledge Transmission and Transformation of Chinese Architecture by Expatriates and Missionaries in Late Qing English and Chinese Newspapers - Mingqi Lu (Religions)
Expatriates and missionaries in China played a significant role in the development and transformation of Chinese architecture in the Late Qing period. However, a systematic comparison of their discourses and proposals on Chinese architecture has been hindered by a lack of historical literature and the complexities of fragmented data and methodologies. This article examines and compares the two most influential non-native newspapers: The North-China Daily News in English, edited by expatriates, and The Review of the Times in Chinese, founded by missionaries. By analyzing these two groups’ discourses and narratives on Chinese architecture, the study explores their similarities and distinctions, revealing the characteristics, strategies, attitudes, interests, and opinions of expatriates, missionaries, and non-missionaries in China on the transmission and transformation of architecture knowledge. The research highlights differences in their preferences for specific text types, subjects, and themes on Chinese architecture, as well as their attitudes toward native and foreign architecture, professional education, and architecture regulations in individual and official spheres. Despite these differences, overlapping characteristics and proposals existed among the three groups. The study further investigates the underlying reasons and mechanisms for their similar or divergent mindsets and behavioral patterns, drawing on human responsive psychology rather than relying on postcolonial or cultural theories.